Water Reuse: A Risk Assessment Model for Water Resources - Rebelo, Anabela; Bento Amaro, Albertina; Quadrado, Felisbina (KnE Materials Science, 2022)
The increasing demands for water for multiple purposes combined with climate change challenges are leading to water scarcity and quality deterioration. Portugal is vulnerable to the impacts of climate change and therefore, the use of reclaimed waters has been identified as a suitable alternative water source for non-potable uses, such as irrigation, to overcome water shortages. In the last two years, new policies for water reuse have been approved at the Portuguese and European levels. The legal frameworks are supported in the international guidelines developed by the International Organization for Standardization, namely for irrigation, urban uses and health risk assessment. In this way, all reuse projects must follow a fit-for-purpose approach, i.e., the water quality needs to meet the requirements of its specific end-uses without compromising public health or the surrounding environment, and all reuse projects must conduct a risk assessment for health and the environment. Quantitative, qualitative or semiquantitative models can be used. Although a quantitative assessment may be desirable, these models tend to be complex and present high uncertainty. Furthermore, these usually require extensive data which are often not available. Accordingly, this study intended to develop a conceptual model to deal with the risk assessment for water resources, namely surface and ground waters. A semi-quantitative approach was employed for the risk characterization, using empirical qualitative judgment to assess the relative importance of hazards, exposure routes, scenarios and barriers in place. The use of a strategic assessment allows the quality standards that meet the needs of each project to be validated. The developed model was applied to a case study to illustrate its applicability. Keywords: water reuse, water resources, risk assessment, semi-quantitative model, compounds of emerging concern